Latar Belakang Pemikiran dan Kiprah Seyyed Hossein Nasr - Titin Nurhidayati (STAIFAS-Press, 2019)
Seyyed Hossein Nasr is one of the Muslims who has expertise in the field of Islamic studies that penetrates scientific barriers to explore Islam as an objective and honest study. His reputation as Professor in the study of the history of science and philosophy shows the depth and sharpness of his thinking. Seyyed Hossein Nasr gave many criticisms of the reality of modern humans today from various aspects. One focus of his criticism is the problem of the phenomenon of modern art which is developing rapidly to all parts of society, including Islamic society. Nasr is also one of the spokespersons of Islam in the West who has been persistent in voicing traditionalism ideas to fortify the flow of modernization that has damaged the joints of the noble traditions of society, especially Islam.